Advancement in the molecular perspective of plant-endophytic interaction to mitigate drought stress in plants - Salvi, Prafull; Mahawar, Himanshu; Agarrwal, Ruchi; Kajal,; Gautam, Vibhav; Deshmukh, Rupesh (Frontiers in Microbiology, 2022)
Change in global climate has started to show its effect in the form of extremes of temperatures and water scarcity which is bound to impact adversely the global food security in near future. In the current review we discuss the impact of drought on plants and highlight the ability of endophytes, microbes that inhabit the plants asymptomatically, to confer stress tolerance to their host. For this we first describe the symbiotic association between plant and the endophytes and then focus on the molecular and physiological strategies/mechanisms adopted by these endophytes to confer stress tolerance. These include root alteration, osmotic adjustment, ROS scavenging, detoxification, production of phytohormones, and promoting plant growth under adverse conditions. The review further elaborates on how omics-based techniques have advanced our understanding of molecular basis of endophyte mediated drought tolerance of host plant. Detailed analysis of whole genome sequences of endophytes followed by comparative genomics facilitates in identification of genes involved in endophyte-host interaction while functional genomics further unveils the microbial targets that can be exploited for enhancing the stress tolerance of the host. Thus, an amalgamation of endophytes with other sustainable agricultural practices seems to be an appeasing approach to produce climate-resilient crops.